2017
DOI: 10.1080/21501203.2017.1419296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of genome-wide plant biomass-degrading CAZymes in white rot, brown rot and soft rot fungi

Abstract: We have conducted a genome-level comparative study of basidiomycetes wood-rotting fungi (white, brown and soft rot) to understand the total plant biomass (lignin, cellulose, hemicellulose and pectin) -degrading abilities. We have retrieved the genome-level annotations of well-known 14 white rot fungi, 15 brown rot fungi and 13 soft rot fungi. Based on the previous literature and the annotations obtained from CAZy (carbohydrate-active enzyme) database, we have separated the genome-wide CAZymes of the selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 70 publications
1
81
0
1
Order By: Relevance
“…Recent genome sequencing studies have also reported about the evolutionary loss of CAZymeencoding genes in few fungal divisions (Skamnioti et al 2008). Comparative metadata analysis of fungal genomewide annotations especially CAZymes has been studied and reported Sista Kameshwar and Qin 2017;Zhao et al 2013). However, previous Page 10 of 19 Sista Kameshwar and Qin Bioresour.…”
Section: Carbohydrate Active Enzymes (Cazymes)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome sequencing studies have also reported about the evolutionary loss of CAZymeencoding genes in few fungal divisions (Skamnioti et al 2008). Comparative metadata analysis of fungal genomewide annotations especially CAZymes has been studied and reported Sista Kameshwar and Qin 2017;Zhao et al 2013). However, previous Page 10 of 19 Sista Kameshwar and Qin Bioresour.…”
Section: Carbohydrate Active Enzymes (Cazymes)mentioning
confidence: 99%
“…The fungal genomic repositories such as joint genome institute MycoCosm (Grigoriev et al 2011;Nordberg et al 2013), 1000 fungal genome project and Hungate collection residing in the rumen microbial genomics network are continuously enhancing the genomic details of various fungi. Studies being conducted to understand the genomic potentials of different fungi belonging to different phyla were compared for their plant cell wall-degrading potentials to explore their applications in biofuel and bioremediation industries King et al 2011;Rytioja et al 2014;Sista Kameshwar and Qin 2017;Zhao et al 2013). Till date, there are 1054 wholegenome sequences of fungi belonging to different phyla in JGI-MycoCosm repository, out of which 444 wholegenome sequences of fungi have been published and publicly available and the remaining 610 whole-genome sequences of fungi were under study and unpublished (Grigoriev et al 2011;Nordberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate-active enzymes (CAZymes) are involved in the polysaccharide degradation of plant cell wall [11], lignin, cellulose, hemicellulose, and pectin [12]. In particular, CAZyme classes (glycoside hydrolases [GH], carbohydrate esterases [CEs], and polysaccharide lyases) play central roles in plant biomass decomposition by bacteria and fungi [13].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate-active enzymes (known as CAZymes) are involved in the degradation processes of polysaccharides of plant cell wall [ 11], lignin, cellulose, hemicellulose and pectin [ 12]. Especially, the CAZyme classes (glycoside hydrolases, carbohydrate eaterases, and polysaccharide lyases) play central roles in plant biomass decomposition by bacteria and fungi [ 13].…”
Section: Introductionmentioning
confidence: 99%